2014
DOI: 10.1016/j.nbd.2013.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Axonal and synaptic failure suppress the transfer of firing rate oscillations, synchrony and information during high frequency deep brain stimulation

Abstract: High frequency deep brain stimulation (DBS) of the subthalamic nucleus (STN) is a widely used treatment for Parkinson's disease, but its effects on neural activity in basal ganglia circuits are not fully understood. DBS increases the excitation of STN efferents yet decouples STN spiking patterns from the spiking patterns of STN synaptic targets. We propose that this apparent paradox is resolved by recent studies showing an increased rate of axonal and synaptic failures in STN projections during DBS. To investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
98
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(104 citation statements)
references
References 77 publications
6
98
0
Order By: Relevance
“…This finding is consistent with a study in brain slices showing that high-frequency stimulation of the motor thalamus could only entrain antidromic activity within corticothalamic axons at firing rates Ͻ50 Hz (Iremonger et al 2006). Similar findings have been reported for other axonal pathways (Jensen and Durand 2009;Rosenbaum et al 2014;Zheng et al 2011) although some fiber tracts, particularly heavily myelinated tracts, can follow high-frequency stimulation pulse trains (Chomiak and Hu 2007).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This finding is consistent with a study in brain slices showing that high-frequency stimulation of the motor thalamus could only entrain antidromic activity within corticothalamic axons at firing rates Ͻ50 Hz (Iremonger et al 2006). Similar findings have been reported for other axonal pathways (Jensen and Durand 2009;Rosenbaum et al 2014;Zheng et al 2011) although some fiber tracts, particularly heavily myelinated tracts, can follow high-frequency stimulation pulse trains (Chomiak and Hu 2007).…”
Section: Discussionsupporting
confidence: 90%
“…Phase-locked spike activity has also been observed distal to the stimulated target with interpulse interval periods exhibiting increased or decreased probability of spiking that is consistent with activation of axonal efferents yielding putatively monosynaptic (Agnesi et al 2013; Anderson et al 2003;Hashimoto et al 2003;Moran et al 2011;Santaniello et al 2015) and multisynaptic (Kita et al 2005;Montgomery 2006) responses. Although axonal conduction fidelity can be robust for the high-stimulation frequencies that are typical of DBS therapy (ϳ80 -185 Hz) (Chomiak and Hu 2007;Windels et al 2003), several studies have shown axonal conduction and synaptic conduction failure (Chomiak and Hu 2007;Iremonger et al 2006;Jensen and Durand 2009;Rosenbaum et al 2014;Zheng et al 2011) with high-frequency stimulation.We hypothesized that 1) the fidelity of spike entrainment to high-frequency stimulation depends on the circuit-level connections to or from current clinical targets of DBS and that 2) the phase-locked spike activity in upstream and downstream cell populations is not stationary over time, with excitatory pathways exhibiting less stationarity than inhibitory pathways. To evaluate the fidelity of frequency entrainment to DBS, we introduce a simple but intuitive measurement called the effective pulse fraction (EPF) representing the number of single-unit spikes, within a phase of an interpulse interval, that are induced or suppressed by stimuli divided by the number of stimulus pulses used to entrain the cell.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, given the oscillatory nature of the train of stimulation pulses employed in DBS, its effects can alter the rhythmic interaction of targeted networks, effectively altering information flow without clearly inhibiting or activating neural tissue (Chiken and Nambu 2014). For instance, axonal and synaptic failures induced by short-term depression following axonal excitation by DBS have been hypothesized to suppress information transfer (Rosenbaum et al 2014). Finally, DBS may induce a regular rhythm driven by high-frequency stimulation that overrides the pathological rhythm present in the target area (Garcia et al 2005).…”
mentioning
confidence: 99%
“…Therefore, it was assumed that STN-HFS moderates the glutamatergic drive to the globus pallidus internus (GPi) and the substantia nigra pars reticulata (SNr) [24]. Rosenbaum et al showed that placement of the electrode and the amplitude of stimulation maximized the number of STN axons activated and will suppress the transfer of -oscillations and synchrony from the STN to GPi [27]. These authors described the following connections between STN and serotonergic neurons of the dorsal raphe nucleus in relation to 5-HT-associated side effects of STN-HFS: The STN receives GABAergic projections from the GPe and has glutamatergic projections to the GPi.…”
Section: Discussionmentioning
confidence: 99%